2020
DOI: 10.1017/s2040174420000598
|View full text |Cite
|
Sign up to set email alerts
|

Post-weaning exposure to high-sucrose diet induces early non-alcoholic fatty liver disease onset and progression in male mice: role of dysfunctional white adipose tissue

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the hepatic manifestation of metabolic syndrome, ranging from simple steatosis to non-alcoholic steatohepatitis (NASH) particularly among chronic consumers of added sugar-rich diets. However, the impact of early consumption of such diets on NAFLD onset and progression is unclear. Thus, this study sought to characterise metabolic factors involved in NAFLD progression in young mice fed with a high-sucrose diet (HSD). Male Swiss mice were fed HSD or regular chow (CTR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
(86 reference statements)
1
5
0
Order By: Relevance
“…In addition, studies with healthy- and normal-weight young male volunteers have demonstrated that high-sucrose (HS) diets augment glucose, low-density lipoprotein, and C-reactive protein quantities [ 9 , 10 ]. Similar observations have been made in rodents following HS diet [ 11 , 12 , 13 , 14 ]. This evidence demonstrates that HS causes important metabolic imbalances, which can result in chronic pathologies such as metabolic syndrome (MS), a major health problem which affects the global population at all ages [ 15 , 16 ].…”
Section: Introductionsupporting
confidence: 84%
“…In addition, studies with healthy- and normal-weight young male volunteers have demonstrated that high-sucrose (HS) diets augment glucose, low-density lipoprotein, and C-reactive protein quantities [ 9 , 10 ]. Similar observations have been made in rodents following HS diet [ 11 , 12 , 13 , 14 ]. This evidence demonstrates that HS causes important metabolic imbalances, which can result in chronic pathologies such as metabolic syndrome (MS), a major health problem which affects the global population at all ages [ 15 , 16 ].…”
Section: Introductionsupporting
confidence: 84%
“…The development of alterations in the male reproductive tract has been associated with sugar consumption and metabolic disorders such as for overweight and obesity (Martini et al, 2010;Sadeghi-Bazargani et al, 2013). The progress of these diseases is characterized by an abnormal or excessive accumulation of lipids in the adipocytes of different deposits of WAT (Cinti et al, 2019), as a result of the consumption of high-calorie diets (França et al, 2020;Oliveira et al, 2020). The PAT is one of its largest fat deposits (Berry et al, 2016) and it is the most important for the testis since its extraction in one or both gonads inhibits spermatogenesis (Chu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In C57BL/6 mice, intake of a high‐sucrose diet (3.79 kcal/g, 53% energy from sucrose) for 10 weeks compared with a diet without sucrose (3.1 kcal/g) increased the amount of WAT, adipocyte size in different WAT depots (mesenteric, subcutaneous, epididymal, and perirenal; Figure 1B), and plasma leptin (26). In addition, male Swiss mice fed a diet high in sucrose (3.51 kcal/g, 30% energy from sucrose) for 60 days compared with mice fed an isocaloric diet low in sucrose (3.46 kcal/g, 11% energy from sucrose) showed higher body weight and lower energy intake, increased retroperitoneal and epididymal WAT, and reduced epididymal WAT lipolysis, all evidence supporting that sucrose can alter WAT mass and function without contributing to excess calories (i.e., an adiposity‐independent effect) (8). The increase in WAT mass associated with sucrose intake might be dependent on excess caloric intake or diet duration (48), because C57BL6J mice fed a sucrose‐enriched diet (3.86 kcal/g, 35% energy from sucrose) did not have increased WAT mass or show increased insulin resistance compared with mice fed an isocaloric diet (3.86 kcal/g, 7% energy from sucrose).…”
Section: Regulation Of Food Intake and Body Weight By Sucrose: Focus ...mentioning
confidence: 96%
“…The adiposity-dependent effect proposes that glucose and fructose obtained from sucrose digestion are only a source of excess calories that cause the WAT expansion and hypertrophy that trigger metabolic dysfunction. In contrast, the adiposity-independent effect proposes that glucose and fructose obtained from sucrose digestion can cause metabolic dysfunction and body weight gain without providing excess calories and causing WAT hypertrophy (7)(8)(9)(10). Animal studies using isocaloric diets rich in sucrose show an adiposity-independent effect of dietary sucrose in regulating food intake and body weight.…”
Section: Introductionmentioning
confidence: 99%